Globalization & National Autonomy: The Experience of Malaysia (ISEAS, 2008)
In a carefully structured, in-depth empirical assessment of the hypothesis that globalization has decisively undermined developing countries' policy autonomy, this volume presents historical reviews of Malaysia's development history in various discrete thematic and policy domains.... the volume is admirably coherent on conceptual terms. The studies show that Malaysia's development agendas have indeed been influenced by global trends, but more clearly reflect a sometime conflicting range of regime interests and domestic political pressures. To the extent that Malaysia's goals have broadly conformed to basic prescriptions of neoliberal globalization, it is significant that those goals were adopted well before global market forces and institutions are typically thought to have robbed developing countries of real choices. The empirically rich policy analyses presented in this volume offer much food for thought about what types of developing countries might engage globalization in similarly empowering ways and how